Peran Bank Sentral dalam Menjaga Stabilitas Moneter - Vina Arifatul Ilmi; Luluk Budi Astutik; Wildatun Hasanah (CV. ITTC INDONESIA, 2024)
The central bank is a country's main financial institution responsible for supervising and managing the monetary and financial system. This is the highest monetary authority tasked with maintaining currency value stability, controlling inflation, and supporting sustainable economic growth. Central banks generally have the authority to set benchmark interest rates, regulate the money supply, and supervise the national banking system Monetary stability is an important foundation for a country's economic health, and central banks play a central role in realizing and maintaining this stability. This research aims to comprehensively analyze the multifaceted role of central banks in maintaining monetary stability, with a focus on mechanisms, challenges and policy implications. Monetary stability refers to the condition in which a country's financial and monetary system functions efficiently and effectively without significant turmoil. It is characterized by a low and stable inflation rate, a relatively stable currency exchange rate, and a reliable financial system. Monetary stability is important because it provides the economic certainty necessary for long-term planning, investment, and sustainable economic growth. Monetary policy is a set of actions and strategies implemented by central banks to manage the money supply and interest rates in the economy. The main objectives of monetary policy are to achieve price stability (control inflation), support economic growth, and maintain financial system stability. Monetary policy can be expansionary (increasing the money supply to stimulate the economy) or contractionary (reducing the money supply to control inflation).